Analisis Faktor-Faktor yang Mempengaruhi Audit Delay Pada Perusahaan Manufaktur Subsektor Minyak dan Gas Bumi Yang Terdaftar di Bursa Efek Indonesia Periode 2020-2024 - Nursidin, M. (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Companies that receive unqualified opinion are considered goodnews (good news) so that the delivery of their financial statements is faster. On the contrary, those that receive unqualified opinions are considered bad news. If the firm receives an unqualified opinion then the audit delay will be shorter compared to the firm receiving other than an unqualified opinion. Profits indicate good news so the company wants to announce the good news faster and conversely if the company suffers a loss then the management wants to postpone the bad news. Companies reporting losses will probably ask the auditor to time their audits longer than usual because this constitutes bad news. On the contrary if the company reports high profits then the company strives for the audited financial statements to be published as soon as possible so that the goodnews is quickly known to the investors and other interested parties. If the firm is experiencing a profit then the audit delay will be getting shorter compared to the firm experiencing a loss.